Starch Synthase IIa-Deficient Mutant Rice Line Produces Endosperm Starch With Lower Gelatinization Temperature Than Japonica Rice Cultivars - Miura, Satoko; Crofts, Naoko; Saito, Yuhi; Hosaka, Yuko; Oitome, Naoko F.; Watanabe, Toshiyuki; Kumamaru, Toshihiro; Fujita, Naoko (Frontiers in Plant Science, 2018)
The gelatinization temperature of endosperm starch in most japonica rice cultivars is significantly lower than that in most indica rice cultivars. This is because three single nucleotide polymorphisms in the Starch synthase (SS) IIa gene in japonica rice cultivars (SSIIaJ) significantly reduce SSIIa activity, resulting in an increase in amylopectin short chains with degree of polymerization (DP)12 compared to indica rice cultivars (SSIIaI). SSIIa forms a trimeric complex with SSI and starch branching enzyme (BE) IIb in maize and japonica rice, which is likely important for the biosynthesis of short and intermediate amylopectin chains (DP≤24) within the amylopectin cluster. It was unknown whether the complete absence of SSIIa further increases amylopectin short chains and reduces gelatinization temperature and/or forms altered protein complexes due to the lack of a suitable mutant. Here, we identify the SSIIa-deficient mutant rice line EM204 (ss2a) from a screen of ca. 1,500 plants of the rice cultivar Kinmaze (japonica) that were subjected to N-methyl-N-nitrosourea mutagenesis. The SSIIa gene in EM204 was mutated at the boundary between intron 5 and exon 6, which generated a guanine to adenine mutation and resulted in deletion of exon 6 in the mRNA transcript. SSIIa activity and SSIIa protein in developing endosperm of EM204 were not detected by native-PAGE/SS activity staining and native-PAGE/immunoblotting, respectively. SSIIa protein was completely absent in mature seeds. Gel filtration chromatography of soluble protein extracted from developing seeds showed that the SSI elution pattern in EM204 was altered and more SSI was eluted around 300 kDa, which corresponds with the molecular weight of trimeric complexes in wild type. The apparent amylose content of EM204 rice grains was higher than that in its parent Kinmaze. EM204 also had higher content of amylopectin short chains (DP≤12) than Kinmaze, which reduced the gelatinization temperature of EM204 starch by 5.6°C compared to Kinmaze. These results indicate that EM204 starch will be suitable for making foods and food additives that easily gelatinize and slowly retrograde.